Influences of un-modulated acoustic inputs on functional maturation and critical-period plasticity of the primary auditory cortex - Zhou, Xiaoming (2008)
Sensory experiences contribute to the development and specialization of signal processing capacities in the mammalian auditory system during a “critical period” of postnatal development. Earlier studies have shown that passive exposure to tonal stimuli during this postnatal epoch induces a large-scale expansion of the representations of those stimuli within the primary auditory cortex (A1) (Zhang et al., 2001). Here, we show that exposing rat pups through the normal critical period epoch and beyond to continuous, un-modulated, moderate-level tones induces no such representational distortion, and in fact disrupts the normal development of frequency response selectivity and tonotopicity all across area A1. The area of cortex responding selectively to continuously exposed sound frequencies was actually reduced, when compared to rats reared in normal environments. Strong exposure-driven plasticity characteristic of the critical period could be induced well beyond the normal end of the critical period, by simply modulating the tonal stimulus. Thus, continuous tone exposure, like continuous noise exposure (Chang and Merzenich, 2003), ineffectively induces critical period plasticity, and indefinitely blocks the closure of a normally-brief critical period window. These findings again demonstrate the crucial role of temporally structured inputs for inducing the progressive cortical maturational changes that result in the closure of the critical period window.